Estudo do comportamento de misturas asfálticas modificadas por borracha de pneus inservíveis - Nunes, Camila Gonçalves Luz (2019)
Due to the improvement of pavements with greater durability, studies have been continuously developed to improve the performance of asphalt mixtures. In this context, the incorporation of residues, such as rubber from tires unserviceable to conventional asphalt mixtures, is shown as a viable alternative for the disposal of these residues and as a possible way to improve the performance of the mixtures. This work aimed to identify the physical and mechanical performance of asphalt mixtures with asphalt-rubber binder, produced in the laboratory, and local aggregates of granitic origin. For the production of asphalt-rubber, 10%, 15% and 20% of rubber content was incorporated into the conventional asphalt binder under high temperature. For the sieve analysis of aggregates of the mixtures, DNIT ES 031/2006 Strip C was used, with adjustments made using the Dominant Size Aggregate Range (DSAR) methodology. After the production of rubber asphalt and definition of aggregate composition, laboratory tests were performed to evaluate the physical and mechanical performance of the mixtures. In order to perform the mechanical tests, the Marshall and SUPERPAVE compaction methods were used, observing the influence of the compaction method on the performance of the mixtures From the obtained results it can be identified that the mixtures produced with incorporation of 10% of rubber to the asphalt binder, and compressed by kneading, according to the SUPERPAVE methodology, presented better mechanical performance.